Lines, loops and spirals: an intraclonal continuum of host location behaviours in walking aphids. (June 2017) - Gottlieb, D.; Inbar, M.; Lombrozo, R.; Ben-Ari, M.
Abstract : A given animal species may employ various strategies to make searching for resources more efficient. In clonal species, in which a parent and its offspring share identical genetic information, survival of even one individual can still ensure the survival of the colony. Thus, clonal species should display a variety of resource-searching strategies rather than discrete behaviours to counter an unknown environment. However, previous studies of host location behaviours of aphids that have dropped from their host plant identified two discrete behaviours: walking in a straight line and turning frequently to search for a nearby plant. We analysed the course characteristics of individuals originating from a single genetic clone of pea aphids, Acyrthosiphon pisum, that dropped to the ground from their host plant. We found that the use of high-resolution behaviour analysis is crucial in determining whether a behavioural phenotype is continuous or discrete. In contrast to previous studies, we found a wide continuum of walking behaviours. While some aphids progressed in a straight line, moving quickly away from the dropping point, others walked in paths with increasing levels of tortuosity. Tortuous paths were characterized by a series of loops (2–18 per path), presumably to locate nearby plants. Each loop took the aphid further from its dropping location. Aphids increased the speed of their searching, so that each loop took the same time to complete. Aphids performing fewer loops increased their speed more rapidly, hinting that the number of loops an aphid performs is determined at the outset of its movement. Aphids performing more loops were more inclined to climb a new host plant. This intraclonal continuum allows dropping aphids to counter the uncertainty of a new and possibly hazardous environment and maximize the probability that at least some individuals will survive and form a new colony. Highlights: Aphids display a continuum of postdropping behaviours as a bet-hedging strategy. Aphids that perform more loops are more inclined to climb a new plant. A few aphids have discrete postdropping behaviours to adapt to extreme environments. High-resolution behaviour analysis is crucial in identifying continuous phenotypes.